2015
DOI: 10.4238/2015.august.28.20
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of CD4+ CD45+ peripheral blood T cells in patients with ulcerative colitis

Abstract: ABSTRACT. The objectives of this study were to explore the expression of peripheral blood CD4+CD45+ T cells in patients with ulcerative colitis (UC) and determine its clinical value. We selected 80 patients with UC from the First Affiliated Hospital of Liaoning Medical University from March 2012 to December 2013. Of these, 27 had mildly active, 28 moderately active, and 25 severely active UC. We also recruited 80 subjects to constitute the healthy control group. The percentages of CD4+CD45+ molecules on the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…CD4 + T cells are an indispensable and important part of it. 17 and Treg cells are different cell subdivisions differentiated by CD4 + T cells under the stimulation of different antigens [10,11]. In recent years, many studies have shown that the imbalance of 17/Treg in peripheral blood is closely related to the onset of UC.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + T cells are an indispensable and important part of it. 17 and Treg cells are different cell subdivisions differentiated by CD4 + T cells under the stimulation of different antigens [10,11]. In recent years, many studies have shown that the imbalance of 17/Treg in peripheral blood is closely related to the onset of UC.…”
Section: Discussionmentioning
confidence: 99%